Carbapenemase producing Klebsiella pneumoniae (KPC) meningitis from chronic otitis media. (2020) - Anwar, Shamsuddin; Acharya, Sudeep; Thapa, Sakura; Rabadi, Jacob; Mobarakai, Neville
Abstract: Meningitis and brain abscess caused by carbapenemase-producing Klebsiella pneumoniae (KPC) is rarely described in the medical literature. Such infections have been described after neurosurgical medium or post-trauma. We describe an unusual case of KPC meningitis originating from with long term intravenous antibiotics.